A mini review on the analytical method and its validation for Psidium guajava (Sciences of Phytochemistry, 2023)
The well-known tropical tree Psidium guajava, also known as the guava, is widely farmed for its fruit. This article consists of literature about various analytical techniques like TLC, UV spectrophotometry, HPLC, and HPTLC that could be used to analyze the Guava plant. The HPLC analysis of Quercetin isolated from the leaves of the guava plant uses a 4 x 125 mm Hypersil ODS column with a mobile phase of 0.5 percent ortho-phosphoric acid in water and methanol at a flow rate of 1ml/min. The column wash times are 20 min and 18 min, respectively. 250C is the temperature in the column. Silica gel 60F 254 pre-coated plates (10x10 cm) were used with toluene: acetone: formic acid (38:10:5) as the solvent system for HPTLC analysis of quercetin obtained from the tender leaves of guava. The λ max was observed in the U.V. spectrum of the isolated compound (quercetin) on three standard wavelengths: 212 nm, 256 nm, and 372 nm. An effort can be made to produce a new analytical method that will be cost-effective and time-saving.